Kepemimpinan Situasional Lasa H.S. Perpustakaan Universitas Muhammadiyah Yogyakarta - Ifonilla Yenianti; Nurjannah Saputri; Yolan Fernando (Jurnal Pustaka Ilmiah, 2021)
The University of Muhammadiyah Yogyakarta (UMY) library is led by Lasa H.S. He has served as the Head of Library of UMY Yogyakarta since 2012 until now. So much various achievements on his leadership in the library and UMY librarians. Lasa H.S be come the Head of Library of UMY during these three periods became the focus of this study. This study uses a qualitative descriptive method using data from interviews, literature studies and documentation. The informants of this study were the head of the UMY library and librarian. The results of this study indicate that the leadership of Lasa H.S. included in the situational leadership style, which fulfills 4 (four) indicators, namely telling, selling, participating, and delegating. Lassa H.S. is a leader who has the characteristics of firm, ambitious, tireless in work but still considers the abilities of his subordinates. lassa. H.S. always provides motivation and support to his subordinates and is ready to help if there are things that are not understood by his subordinates.